Korean red ginseng attenuates doxorubicin-induced testicular dysfunction in rats by modulating inflammatory, oxidative, and autophagy responses - Cha, Kyu-Min; Kopalli, Spandana Rajendra; Han, Sang Yun; Lee, Sang-Ho; Jeong, Min-Sik; Cho, Jae Youl; Han, Chang-Gyun; Lee, Seung-Ho; Kim, Soo-Nam; Kim, Jin-Chul; Kim, Si-Kwan (ELSEVIER SCIENCE BV, 2018)
The effect of Korean red ginseng (KRG; Panax ginseng Meyer) against doxorubicin (DOX)-induced testicular inflammation was investigated. Male Sprague-Dawley rats were treated with DOX (1 mg mL(-1) kg(-1) week(-1); intra-peritoneally) for 8 weeks, and KRG water extract (EX1; 100 and EX2; 200 mg/kg/day; orally) was administered for 9 weeks starting one week before DOX exposure. The expression levels related to spermatogenesis, inflammatory and autophagy markers were evaluated using western blotting and reverse transcriptase polymerase chain reaction. DOX-induced a significant (p < .05) alteration in the expression of antioxidation spermatogenesis and sex hormone receptors genes when compared with control groups, which were attenuated with KRG-WE treatment significantly (p < .05 similar to p < .01). KRG-WE also ameliorated the DOX-induced alteration in pro-inflammatory cytokines via the mitogen-activated protein kinases/nuclear factor kappa-B pathway and autophagy in the testes of rats. In conclusion, KRG might be used as a functional food for prevention of chemotherapy -induced testicular inflammation.
Keywords: TUMOR-NECROSIS-FACTOR; NF-KAPPA-B; PANAX-GINSENG; AGED RATS; HEART-FAILURE; CANCER CELLS; GUINEA-PIGS; GINSENOSIDES; STRESS; INHIBITION